[OP.4B.06] THE IMPACT OF UPDATED LEFT VENTRICULAR GEOMETRY CLASSIFICATION ON RIGHT VENTRICULAR REMODELLING IN A HYPERTENSIVE POPULATION. (September 2016) - Tadic, M.; Cuspidi, C.; Vukomanovic, V.; Kocijancic, V.; Celic, V.
Abstract : Objective: We aimed to investigate right ventricular (RV) mechanics and function in hypertensive patients with different left ventricular (LV) geometric patterns by using a two-dimensional (2D) strain analysis and three-dimensional echocardiography (3D). Design and method: This cross-sectional study included 232 hypertensive subjects who underwent complete 2D and 3D examination. We applied the updated classification of LV geometry that considers LV mass index (LVMI), LV end-diastolic volume (LVEDV) index and relative wall thickness (RWT). All the subjects were divided into 6 groups: normal LV geometry, concentric remodelling, eccentric LVH, concentric LVH, dilated LVH and concentric-dilated LVH. Results: According to the updated classification, the study sample included 98 subjects with normal LV geometry (42%), 32 patients with LV concentric remodeling (14%), 49 with eccentric LVH (21%), 36 concentric LVH (15%), 11 dilated LVH (5%) and 6 concentric-dilated LVH (3%). 3D RV end-diastolic and end-systolic volume indexes gradually and significantly increased from the subjects with normal LV geometry and LV concentric remodelling, across patients with eccentric and concentric LVH, to participants with dilated and concentric-dilated LVH (61 ± 6 vs. 63 ± 6 vs. 68 ± 8 vs. 67 ± 7 vs. 77 ± 8 vs. 74 ± 8 ml/m2 for RV end-diastolic volume index, p < 0.001), whereas 3D RV ejection fraction gradually decreased in the same direction (59 ± 4 vs. 59 ± 3 vs. 58 ± 3 vs. 57 ± 3 vs. 55 ± 3 vs. 54 ± 3 %, p < 0.001). Global RV longitudinal strain was significantly decreased in patients with concentric and concentric-dilated LVH comparing to subjects with normal LV geometry and concentric LV remodelling (−24.0 ± 3.5 vs. −23.7 ± 3.3 vs. −22.5 ± 3.1 vs. −20.7 ± 2.6 vs. −21.4 ± 2.9 vs. −20.5 ± 2.5 %, p < 0.001). Conclusions: 2D RV myocardial deformation and 3D RV function are significantly impacted by LV geometry in hypertensive patients. Concentric and concentric-dilated LVH patterns have the greatest unfavourable effect on RV mechanics.